Hubungan Pengetahuan SADARI (Pemeriksaan Payudara Sendiri) Sebagai Perilaku Deteksi Dini Ca Mamae Pada Ibu Fatayat - Lilik Darwati; Khusnul Nikmah; Mersya Nur Avivah Aziz (EMBRIO: Jurnal Kebidanan, 2022)
Cancer is one of the main causes of morbidity and mortality worldwide. Breast cancer screening is an examination or attempt to find abnormalities that lead to breast cancer in a person or group of people who have no complaints. The initial effort to do a Mamae ca screening is by BSE or breast self-examination. BSE is an individual effort or each woman. The purpose of this research is to find out whether there is a relationship between awareness knowledge as early detection behavior ca Mamae. The research design used was observational analysis. The sampling technique used was purposive sampling. Data were collected by means of a questionnaire and analysis was performed by calculating the Chi-Square test (square (a = 0.05). The results of respondents who had a good level of knowledge were 51 mothers (92.7%) and 41 mothers (74.5%) who did breast self-examination. And based on the chi-square test, it was found that the p-value (0.047). This shows that the level of knowledge has a significant relationship with breast self-examination behavior because a value is smaller than the p value, namely the p value (0.047) < a (0.05).